Improving Market Transparency via a Web-Based Food Price Monitoring System - Indra Indra (Jurnal Responsive Teknik Informatika, 2025)
This study aims to design and develop a web-based food price monitoring system in Regency X to address delays and data inaccuracies found in conventional systems. A qualitative descriptive approach is employed using the Waterfall system development method, encompassing requirements analysis, system design, implementation, and testing. Primary data are collected through interviews and observations in traditional markets, while secondary data are obtained from official documents. The system is designed using Unified Modeling Language (UML) and developed with PHP and MySQL. White Box and Black Box testing results indicate that the system operates in accordance with user requirements, with a high level of user satisfaction based on survey results. The system enables real-time monitoring of food prices, accelerates information dissemination, and enhances transparency in the local market. In conclusion, the system effectively supports decision-making related to food price control; however, further development such as automatic data integration and price prediction features is still required.